(untitled) (Global Journal of Human-Social Science, 2024)
The article deals with the importance of colour among populations of several different countries around the world choices of colour schemes in residential interiors of these countries as well as common and distinctive features in colour schemes of interiors The purpose of the study is to examine compare and analyse the colour schemes of residential interiors in Japan Germany Finland and Ukraine Methodology The main methods of the study are the following empirical theoretical and empirical-theoretical The empirical method includes observation comparison and generalisation The theoretical method encompasses progressing from the abstract to the concrete abstraction concretization identification and differentiation Much of the work was carried out using empirical and theoretical methods in particular comparative analysis induction and deduction